A systematic review of congenital external ear anomalies and their associated factors - Acosta-Rodríguez, Alejandro; Reza-López, Sandra A.; Aguilar-Torres, César R.; Hinojos-Gallardo, Luis C.; Chávez-Corral, Dora V. (Frontiers in Pediatrics, 2025)
ObjectiveExternal ear anomalies may lead to conductive hearing loss with significant childhood disability, psychological distress, anxiety, social avoidance, and behavioral problems. The aim of this study is to compile and review published literature on the frequency of isolated and non-isolated external ear anomalies, their associated factors, and associated malformations/deformations in non-isolated cases.MethodsWe conducted a systematic review in PubMed, Google Scholar, and Science Direct searching for any type of article (excluding reviews and meta-analyses) reporting isolated and non-isolated external ear anomalies in humans. Two authors extracted the information according to the main variables of interest according to PICO criteria. Details of studied population and main findings were also obtained (malformation type, unilateral or bilateral malformations and associated factors).ResultsTwenty-six studies met eligibility criteria to be included in this review. Anotia/microtia was the most reported malformation, more frequently found in males, mostly unilateral; being the right ear the most affected, and more frequent in Hispanic population. Associated factors for external ear anomalies included parental age, maternal education, multiple pregnancies, high maternal body mass index and diabetes, pregnancy, and perinatal complications (low birth weight, prematurity, threatened abortion, etc.), twining, and chemical/drug exposure. The most reported malformations and syndromes associated with congenital external ear defects included: skull/face anomalies, cleft lip/palate, congenital heart defects, musculoskeletal malformations of skull, face and jaw, Treacher-Collins, OAVS (oculo-auriculo-vertebral spectrum), and trisomy 18, 13 and 21.ConclusionCongenital external ear anomalies can occur isolated or associated with other malformations or syndromes. Environmental, socioeconomic, and cultural factors may partially explain the variation across populations for congenital external ear anomalies. Depending on their type and severity, they can lead to speech impediments and childhood disability, particularly in bilateral cases, highlighting the relevance of early detection and repair to avoid childhood disability.